Cashew nut shell liquid as a green alternative to functionalize polymers: experimental and modeling investigation - Costa, Laura Pires da Mata (2019)
Cashew nut shell liquid (CNSL) is a by-product of cashew nut industry. Despite this, it is rich in phenolic compounds that can be used as comonomers in the functionalization of polymers. In the present study, the radical polymerization of these materials is investigated. Inittialy, the bulk copolymerization of cardanol or natural CNSL with styrene, methyl methacrylate, vinyl acetate or acrylic acid was studied kinetically and several analyzes were carried out to characterize the copolymers formed. Some advantages obtained in the copolymerization were the increase in thermal stability and reduction of the glass temperature of the polymers. Thus, a kinetic mechanism was proposed and a mathematical model derived to estimate kinetic paramers that allowed proper description of monomer conversion, average molecular weights, and composition of the copolymers. It is detected that the renewable monomers exert a strong inhibition effect on the polymerizations, making the incorporation of them into the copolymer chains difficult, but not impossible. With these results, suspension polymerizations were performed with the conditions that obtained the best results in bulk polymerization. Polymers previously hydrophobics became more hydrophilic; and the addition of cardanol in such polymerization has proved to be an excellent alternative for particle size control and to stabilize suspensions for long periods of time.